2013
DOI: 10.1093/cercor/bhs388
|View full text |Cite
|
Sign up to set email alerts
|

Brain Reactivity Differentiates Subjects with High and Low Dream Recall Frequencies during Both Sleep and Wakefulness

Abstract: The neurophysiological correlates of dreaming remain unclear. According to the "arousal-retrieval" model, dream encoding depends on intrasleep wakefulness. Consistent with this model, subjects with high and low dream recall frequency (DRF) report differences in intrasleep awakenings. This suggests a possible neurophysiological trait difference between the 2 groups. To test this hypothesis, we compared the brain reactivity (evoked potentials) of subjects with high (HR, N = 18) and low (LR, N = 18) DRF during wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
121
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 88 publications
(141 citation statements)
references
References 61 publications
20
121
0
Order By: Relevance
“…These data confirmed that regions involved in the regulation of emotional memory may be the same across sleep and wakefulness. As a further support to this hypothesis, a PET study disclosed that High Recallers (HR) showed a greater regional cerebral blood flow (rCBF) in temporoparietal junction (TPJ) and medial prefrontal cortex than Low Recallers (LR; Eichenlaub et al 2014b). This region is involved in the "Default Mode Network" (DMN), activated during resting state, daydreaming and mental imagery processes (Desseilles et al 2011;Domhoff 2011;Eichenlaub et al 2014b).…”
Section: Discussionmentioning
confidence: 90%
“…These data confirmed that regions involved in the regulation of emotional memory may be the same across sleep and wakefulness. As a further support to this hypothesis, a PET study disclosed that High Recallers (HR) showed a greater regional cerebral blood flow (rCBF) in temporoparietal junction (TPJ) and medial prefrontal cortex than Low Recallers (LR; Eichenlaub et al 2014b). This region is involved in the "Default Mode Network" (DMN), activated during resting state, daydreaming and mental imagery processes (Desseilles et al 2011;Domhoff 2011;Eichenlaub et al 2014b).…”
Section: Discussionmentioning
confidence: 90%
“…During sleep, between-group differences were also observed for auditory evoked potentials (AEPs) to the same stimuli, at the latency of the P3a in N2 and at later latencies during all sleep stages. Finally, at the behavioral level HR showed more intra-sleep wakefulness (ISW) than LR (~15 min more on average, see Eichenlaub et al, 2014a). …”
Section: Introductionmentioning
confidence: 97%
“…For more than a century, researchers have investigated whether some psychological parameters could explain dream recall frequency variability (for a review see Ruby, 2011), but it’s only recently that physiological parameters have been considered. Using Electroencephalogram (EEG) and PET we found neurophysiological differences between high dream-recallers (HR) and low dream-recallers (LR) during both sleep and wakefulness (Ruby et al, 2013b; Eichenlaub et al, 2014a,b). Notably, during wakefulness, in response to auditory novel stimuli, the attention-orienting brain response (P3a) and a late parietal component were found to be larger in HR than in LR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data used in this study consists of polysomnographic (PSG) records in 15 healthy subjects aged 29.2 ± 8 years, which were collected at the DyCog Lab of the Lyon Neuroscience Research Center (Lyon, France) as part of a larger study exploring cognition during sleep (Eichenlaub et al, 2012(Eichenlaub et al, , 2014Ruby et al, 2013a,b). Each record contains EOG, EMG and 21 scalp-EEG channels.…”
Section: Polysomnographic Data Basementioning
confidence: 99%